2015
DOI: 10.4103/0970-9290.162880
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 8-hydroxydeoxyguanosine as a marker of oxidative stress induced genetic toxicity in oral cancer patients

Abstract: Urinary 8-OHdG can be a useful diagnostic marker of oxidative DNA damage in oral cancer subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Oxidative DNA damage induced by reactive oxygen species (ROS) plays a pivotal role in the nosogenesis of respiratory disease such as lung cancer and asthma [1, 2]. ROS, resulting from chemical compounds or the action of exogenous physical factors such as ultraviolet A, or the metabolism of cells, can induce a great many DNA damage, including base modification and DNA strand breaks [3], were generally believed to be involved in the carcinogenic mechanism [4, 5]. Previous studies have shown that 8-hydroxy- 2′- deoxyguanosine (8-OHdG) is a widely accepted biomarker for assessing the extent of oxidative damage to DNA [6].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative DNA damage induced by reactive oxygen species (ROS) plays a pivotal role in the nosogenesis of respiratory disease such as lung cancer and asthma [1, 2]. ROS, resulting from chemical compounds or the action of exogenous physical factors such as ultraviolet A, or the metabolism of cells, can induce a great many DNA damage, including base modification and DNA strand breaks [3], were generally believed to be involved in the carcinogenic mechanism [4, 5]. Previous studies have shown that 8-hydroxy- 2′- deoxyguanosine (8-OHdG) is a widely accepted biomarker for assessing the extent of oxidative damage to DNA [6].…”
Section: Introductionmentioning
confidence: 99%